Contextualization of chemistry teaching through the determination of alcohol content in beverages - reports of activities developed in the junior scientific initiation project (Research, Society and Development, 2025)
The motivation for developing this project was the fact that young people are increasingly exposed to alcoholic beverages, combined with the fact that teaching chemistry through traditional strategies makes learning tiring and demotivating. This article aimed to show an experience report on the study Application of Chemistry Concepts and Techniques as a Tool for Quantifying Alcohol Content in Beverages. The study was developed in a public school in São Mateus and Ceunes with 5 students in the 2nd year of high school. Active methodologies were used to teach chemistry using a contextualized and investigative approach to content with an experimental character. The following content shows: divisions of chemistry, significant digits, expression of results, stoichiometric calculations, chemical reactions, laboratory glassware, methods for separating mixtures, and preparing and expressing the concentration of solutions. Strategies such as educational games and consolidation exercises were used to stimulate student interest and assess learning. These teaching activities promote greater engagement and enable effective verification of understanding of concepts. The results obtained were significant learning, with the promotion of students as protagonists in the process of acquiring knowledge. They were more aware and critical of the harm caused by the consumption of alcoholic beverages. The project also proposed bringing high school students closer to the university environment, a result that was consolidated when they entered undergraduate courses.